The contribution of 3D quantitative meniscal and cartilage measures to variation in normal radiographic joint space width—Data from the Osteoarthritis Initiative healthy reference cohort. Issue 87 (February 2017) - Roth, Melanie; Wirth, Wolfgang; Emmanuel, Katja; Culvenor, Adam G.; Eckstein, Felix
Abstract: Objective: To explore to what extent three-dimensional measures of the meniscus and femorotibial cartilage explain the variation in medial and lateral femorotibial radiographic joint space width (JSW), in healthy men and women. Methods: The right knees of 87 Osteoarthritis Initiative healthy reference participants (no symptoms, radiographic signs or risk factors of osteoarthritis; 37 men, 50 women; age 55.0 ± 7.6; BMI 24.4 ± 3.1) were assessed. Quantitative measures of subregional femorotibial cartilage thickness and meniscal position and morphology were computed from segmented magnetic resonance images. Minimal and medial/lateral fixed-location JSW were determined from fixed-flexion radiographs. Correlation and regression analyses were used to explore the contribution of demographic, cartilage and meniscal parameters to JSW in healthy subjects. Results: The correlation with (medial) minimal JSW was somewhat stronger for cartilage thickness (0.54 ≤ r ≤ 0.67) than for meniscal (−0.31 ≤ r ≤ 0.50) or demographic measures (−0.15 ≤ r ≤ 0.48), in particular in men. In women, in contrast, the strength of the correlations of cartilage thickness and meniscal measures with minimal JSW were in the same range. Fixed-location JSW measures showed stronger correlations with cartilage thickness (r ≥ 0.68 medially; r ≥ 0.59 laterally) than with meniscal measures (r ≤ |0.32| medially; r ≤ |0.32| laterally). Stepwise regression models revealed that meniscal measures added significant independent information to the total variance explained in minimal JSW (adjusted multiple r 2 = 58%) but not in medial or lateral fixed-location JSW (r 2 = 60/51%, respectively). Conclusions: In healthy subjects, minimal JSW was observed to reflect a combination of cartilage and meniscal measures, particularly in women. Fixed-location JSW, in contrast, was found to be dominated by variance in cartilage thickness in both men and women, with somewhat higher correlations between cartilage and JSW in the medial than lateral femorotibial compartment. The significant contribution of the meniscus' position on minimal JSW reinforces concerns over validity of JSW as an indirect measure of hyaline cartilage.